Respuesta :
(2.3 x 10^-3)(3 x 10^8)
=(2.3 x 3)(10^-3 x 10^8)
= 6.9 x 10^5
hope it helps
=(2.3 x 3)(10^-3 x 10^8)
= 6.9 x 10^5
hope it helps
Answer:
Scientific notation of [tex](2.3\times 10^{-3})\times (3\times 10^{8})[/tex] is [tex]6.9\times 10^{5}[/tex] .
Step-by-step explanation:
As given the expression in the question be as follow .
[tex]= (2.3\times 10^{-3})\times (3\times 10^{8})[/tex]
Simplify the above terms
[tex]= 2.3\times 10^{-3}\times 3\times 10^{8}[/tex]
[tex]= 2.3\times 3\times 10^{-3}\times 10^{8}[/tex]
Now by using the exponent property
[tex]x^{a}\times x^{b} = x^{a + b}[/tex]
Thus apply this property in the above
[tex]= 6.9\times 10^{-3+8}[/tex]
[tex]= 6.9\times 10^{5}[/tex]
Therefore  scientific notation of [tex](2.3\times 10^{-3})\times (3\times 10^{8})[/tex] is [tex]6.9\times 10^{5}[/tex] .